On the complex relationship between Law and trust - Ansuátegui Roig, Francisco Javier (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
This article is part of the monographic section "Derecho y confianza”In this paper I analyse Tommaso Greco’s proposal regarding the relationshipbetween Law and trust, focusing on some relevant points and showing itscomplex and multidimensional nature; and showing some consequences relatedto the concept of Law.
Keywords: trust; sanction; ethics; conflict; security